2016
DOI: 10.1007/s00464-016-5321-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes after TEM in patients with complete clinical response after neoadjuvant chemoradiotherapy

Abstract: TEM may be an alternative treatment for patients with rectal cancer who exhibit a complete clinical response to neoadjuvant chemoradiotherapy because it offers the possibility to achieve a full thickness excision of the rectal wall. TEM also allows the identification of any residual disease and provides optimal quality of life and functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, radical surgery is difficult to perform, especially for initially unresectable advanced colon cancer and mid‐low rectal cancer . Preoperative radiotherapy is widely used to downstage tumors to lower treatment failure, but the local recurrence and outcome remain variable, which indicates significant differences in tumor response to radiation . Therefore, it is essential to explore the molecular mechanisms of CRC cell survival following irradiation treatment, and, furthermore, there is an urgent need to identify useful molecular targets to improve the response of CRC to local irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, radical surgery is difficult to perform, especially for initially unresectable advanced colon cancer and mid‐low rectal cancer . Preoperative radiotherapy is widely used to downstage tumors to lower treatment failure, but the local recurrence and outcome remain variable, which indicates significant differences in tumor response to radiation . Therefore, it is essential to explore the molecular mechanisms of CRC cell survival following irradiation treatment, and, furthermore, there is an urgent need to identify useful molecular targets to improve the response of CRC to local irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…This same cohort also reported worse QOL related to fecal incontinence (58). One study found an association between incidence of radiation proctitis and worsening anorectal function (59). On the other hand, a study Coco et al suggested that even though there might be a trend toward increased short-term morbidity in patients receiving preoperative LC-CRT, there was no difference in sphincter function; this study however, did not include data regarding patient impact, potentially biasing towards a null result (54).…”
Section: Quality Of Life After Preoperative Chemoradiation and Organ-sparing Surgery (Local Excision)mentioning
confidence: 72%
“…However, it does not seem to affect the continence status after one year from surgery [ 158 161 ]. Age and gender could be additional factors to influence anorectal function [ 134 ].…”
Section: Resultsmentioning
confidence: 99%